The relationship between family support and medication adherence among elderly hypertensive patients at the outpatient clinic of Puskesmas Poigar - Sintia Natasya Kessek; Hanim Mufarokhah; Apriyani Puji Hastuti (Indonesian Journal of Health Science, 2026)
Hypertension is a common chronic condition among the elderly and requires long-term medication adherence to prevent complications. This study aimed to determine the relationship between family support and medication adherence among elderly patients with hypertension at the Outpatient Clinic of Puskesmas Poigar. A quantitative method with a correlational analytic design and a cross-sectional approach was used. The sample consisted of 60 respondents selected through accidental sampling. Data were collected using a modified family support questionnaire and the MMAS-8 medication adherence scale, then analyzed using univariate and bivariate tests with the Chi-square test at a significance level of α = 0.05. The findings showed that most respondents had high family support (41.7%) and high medication adherence (45.0%). The Chi-square test revealed a significant relationship between family support and medication adherence (p = 0.007), indicating that elderly individuals receiving strong family support were more likely to adhere to antihypertensive therapy. These results highlight the essential role of family involvement in improving treatment adherence among elderly hypertensive patients and the need to integrate family-based interventions into community nursing services.